Successive introduction of four new vaccines in Rwanda: High coverage and rapid scale up of Rwanda's expanded immunization program from 2009 to 2013. Issue 29 (17th June 2016) - Gatera, Maurice; Bhatt, Sunil; Ngabo, Fidele; Utamuliza, Mathilde; Sibomana, Hassan; Karema, Corine; Mugeni, Cathy; Nutt, Cameron T.; Nsanzimana, Sabin; Wagner, Claire M.; Binagwaho, Agnes
Highlights: We present information on Rwanda's rollout of four new vaccines in 5 years. Careful planning and widespread messaging were used prior to each rollout. Trained community health workers informed the population of each campaign. Community health workers helped to forecast the target populations. Rwanda's experience with rapid rollouts may be useful to other countries. Abstract: As the pace of vaccine uptake accelerates globally, there is a need to document low-income country experiences with vaccine introductions. Over the course of five years, the government of Rwanda rolled out vaccines against pneumococcus, human papillomavirus, rotavirus, and measles & rubella, achieving over 90% coverage for each. To carry out these rollouts, Rwanda's Ministry of Health engaged in careful review of disease burden information and extensive, cross-sectoral planning at least one year before introducing each vaccine. Rwanda's local leaders, development partners, civil society organizations and widespread community health worker network were mobilized to support communication efforts. Community health workers were also used to confirm target population size. Support from Gavi, UNICEF and WHO was used in combination with government funds to promote country ownership and collaboration. Vaccination was also combined with additional community-based health interventions. Other countries considering rapid consecutive or simultaneous rollouts of new vaccines may consider lessons from Rwanda's experience while tailoring the strategies used to local context.